Dancing around the pole: holarctic phylogeography of the Arctic fairy shrimp Branchinecta paludosa (Anostraca, Branchiopoda) - Lindholm, Markus; Angles d'Auriac, Marc; Thaulow, Jens; Hobæk, Anders (Hydrobiologia, 2018)
The distributional patterns of Arctic species are commonly affected by the recurring Pleistocene glaciations, which contributed to transient or permanent genetic isolation. Here we explore the phylogeography of the climate-sensitive Arctic fairy shrimp Branchinecta paludosa, which has a circumpolar range of distribution, with certain southern alpine outreaches. We sequenced the mitochondrial cytochrome oxidase I subunit from samples collected at ten Nearctic and nine Palaearctic sites, including southern alpine populations. A handful of ambiguous bases in certain sequences strongly suggested heteroplasmy, possibly being reported for the first time in anostracans. Evolutionary analysis of the sequence variations showed a temporal divergence coinciding with the flooding of the Beringia land bridge. Sequence alignment with outgroup taxa for phylogenetic analysis showed three distinct major clades, reflecting geographical isolation. The most divergent clade, from isolated alpine ponds in the Rocky Mountains, probably represents a different and undescribed species. Two other major clades corresponded to the geographical areas of Nearctic and Palaearctic. Finally, the southern Palaearctic outstretch showed genetic separation, most likely representing a geographical and climatic isolated relict population. publishedVersion